KELAYAKAN USAHA BUDIDAYA RUMPUT LAUT EUCHEUMACOTTONII DENGAN METODE LONG LINE - Tarmaji Antowijoyo; Yuliyanto; RR. Yulianti Prihatiningrum; Fifi Swandari (Universitas Lambung Mangkurat, 2017)
The purpose of this study is twofold. First, assess the feasibility of seaweed cultivation. Second, identify the key internal and external factors affecting the cultivation of seaweed. The hope can be formulated business development strategy to be applied seaweed cultivators. The method used in this study is a research approach that is both quantitative and qualitative descriptive analysis to describe and analyze the prospects, potential and direction of development of seaweed cultivation. Data collection was conducted through a survey directly to businesses through the research questionnaire and also through interviews and discussion groups (Focus Group Discussion /FGD) with farmers. The results of the feasibility assessment methods NPV, Net Benefit Cost Ratio (Net B/C), IRR, Payback Period and BEP show that seaweed cultivation is feasible. SWOT assessment results show that the cultivation is in quadrant S-O (Strength-Opportunity), so that strategies can be done is Aggressive. This means that the powers that be should seek to take advantage of existing opportunities. Some do like: seaweed produces higher quality and made of processed seaweed products such as candy and dodol seaweed. The market for both types of products is relatively large. Some stakeholders can help farmers master the necessary skills.